2015
DOI: 10.5114/pm.2015.56402
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the level of antibodies against heat shock proteins 60 during different hormonal protocols in postmenopausal women

Abstract: IntroductionIn current literature, the immune-inflammatory theory of atherosclerosis is widely discussed. The role of how heat shock proteins 60 (HSP60) lead to the development of the atheromatous plaque is especially underlined. The aim of the study is to estimate the influence of three hormonal protocols on behavior of antibodies against HSP60. It determines the state of endothelium in postmenopausal women.Material and methodsThe study was carried out on 90 women between 2007 and 2012. All the women were in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…This finding is in line with previous in vitro evidence describing maximum HSP60 production after the ovulation, immediately following the peak of FSH values observed within the menstrual cycle (Neuer et al, 2000). In line with this observation, a small interventional study of 90 postmenopausal women reported a significant reduction in titers of antibodies against HSP60 in women receiving treatment with hormone replacement as opposed to control (Rajtar-Ciosek et al, 2015) suggesting a hormonal regulation of HSP-levels.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with previous in vitro evidence describing maximum HSP60 production after the ovulation, immediately following the peak of FSH values observed within the menstrual cycle (Neuer et al, 2000). In line with this observation, a small interventional study of 90 postmenopausal women reported a significant reduction in titers of antibodies against HSP60 in women receiving treatment with hormone replacement as opposed to control (Rajtar-Ciosek et al, 2015) suggesting a hormonal regulation of HSP-levels.…”
Section: Discussionsupporting
confidence: 90%